Vegetation Association of Bird of Paradise Community in Berber Village Forest, West Bonggo District, Sarmi Regency, Papua Province Indonesia - Raunsay, Edoward Krisson; Koirewoa, Dolfina Costansah; Jesajas, David Reinhard; Nurcholis, Waras (Indonesian Journal of Contemporary Multidisciplinary Research, 2024)
This research aims to determine the richness, diversity and dominance of tree and bird species, as well as analyzing the relationship between trees and bird communities in the Berber Village forest.  Data collection methods include observation, exploration and Concentration Counts. Species richness analysis uses the Margalef Index. Diversity index, with the Shannon-Wiener equation, Dominance index using the dominance index. Assessment of the ecological function of trees using four assessment categories (very good, good, moderate and poor). A total of 36 individuals were observed, consisting of 23 males and 13 females. The richness of birds of paradise in Berber village forests is in the low category (0.4343) and is dominated by P. minor. Activity P. minor observed at various heights ranging from 21 to 64 meters above sea level (masl). Distribution of Bird of Cenderawasih activity (P. minor And C. king) shows a predilection for certain tree types and variations in height.